Limitations of structuring of cross-border mergers and acqusitions in accounting for market expectations - М. С. Мишин (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2014)
Market expectations have an impact on value of M&A deals, especially on cross-border deals due to higher degree of uncertainty and greater average deal size. Positive market reaction, expressed in growth of a buyer’s market capitalization, indicates that market has more optimistic view on expected financial results of the companies after the merger than buyer has. On the other hand, negative market reaction indicates a possible overestimation of future financial results of the M&A deal by the buyer. In both cases there is a change in market capitalization of the buyer at a moment of public announcement, which is an indirect benefit or cost of the deal for shareholders. Existing approaches to cross-border M&A valuation don’t take into account the impact of market reaction on total deal value and market value of acquirer, and are based only on fundamental factors such as profitability, sales growth rates, cash flows and leverage. In deal structuring market expectations are not accounted and market reaction realized in change of acquirer’s market capitalization is considered to be an uncontrolled loss or benefit which doesn’t influence M&A deal value. Therefore the effect of market expectations impact is not currently taken into account in a consideration structure of mergers and acquisitions. Structuring of cross-border M&A deals should be improved by including additional conditional component which would consider losses of acquirer’s market capitalization as a result of negative market reaction to the deal.